Fertility recovery despite the COVID-19 pandemic in Finland? - Jessica Nisén; Marika Jalovaara; Anna Rotkirch; Mika Gissler (The Society of Social and Economic Research in the Universities of Turku, 2025)
Finland’s increase in births, recorded in the months following the first two waves of the COVID-19 pandemic, was among the strongest. We assess whether this fertility increase occurred because of or despite the pandemic, or both, by investigating the country’s fertility trends by women’s region of residence, age group, and parity. Finland overall was modestly hit by the early pandemic, but Helsinki-Uusimaa faced more severe restrictions. We used aggregate register data until September 2021 to assess monthly fertility. In 2020 and 2021, the relative increases in fertility were strongest among women aged 30 and over. In 2021, but not in 2020, fertility increased most in Helsinki-Uusimaa, and across parities. Model-based estimates suggested a modest fertility boost of the early pandemic. To conclude, Finland’s notable fertility increase in 2021 broadly followed pre-existing trends where the country recovered from its all-time low fertility levels, and the early pandemic may have reinforced this trend.